PENINGKATAN EKSISTENSI BLOGGER MELALUI KOMUNITAS VIRTUAL (AN INCREASE OF BLOGGER EXISTENCE THROUGH VIRTUAL COMMUNITY) - Intyaswati, Drina; M. B. P., Ratu Laura (Jurnal The Messenger, 2017)
As a writer (blogger) would be exist with as a member of a virtual community, because it will add who can access his writings. The purpose of this paper is, to know the role of virtual community in the existence of bloggers and how it can improve the productivity of writings. This study used emak2blogger.com website as study material. The method used is descriptive qualitative with interview informans to describe the virtual community Kumpulan Emak Blogger (KEB) and also content analysis. The results showed that there is better existence as a blogger for KEB members, since the blogger has a place that is able to express their creativity. By joining the KEB knowledge and ability of writing in a blog be increased, and also the increased blog traffic. Group communication contained in community KEB, in addition, interpersonal communication was used by members of KEB to communicate intensively.